On the path toward organic spintronics. (15th July 2014) - Moodera, Jagadeesh S.; Koopmans, Bert; Oppeneer, Peter M.
Abstract: Abstract : Organic materials provide a unique platform for exploiting the spin of the electron—a field dubbed organic spintronics. Originally, this was mostly motivated by the notion that because of weak spin-orbit coupling, due to the small mass elements in organics and small hyperfine field coupling, organic matter typically displays a very long electron spin coherence time. More recently, however, it was found that organics provide a special class of spintronic materials for many other reasons—several of which are discussed throughout this issue. Over the past decade, there has been a growing interest in utilizing the molecular spin state as a quantum of information, aiming to develop multifunctional molecular spintronics for memory, sensing, and logic applications. The aim of this issue is to stimulate the interest of researchers by bringing to their attention the vast possibilities not only for unexpected science but also for the enormous potential for developing new functionalities and applications. The six articles in this issue deal with some of the breakthrough work that has been ongoing in this field in recent years.